P11.33 Characterization of a new patient-derived metastatic glioblastoma cell line and response to sodium selenite anticancer agent: in vitro results and preclinical data in mice. (6th September 2019) - Larrouquere, L; Berthier, S; Col, E; Lefebvre, C; Cottet-Rousselle, C; Chovelon, B; Garrel, C; Boutonnat, J; Faure, P; Hazane-Puch, F
Abstract: BACKGROUND: Glioblastoma (GBM) are very heterogeneous, organized in a hierarchical pattern, including cancer stem cells (CSC), and are responsible for development, maintenance, and cancer relapse. Therefore, it is relevant to establish new GBM cell lines with CSC characteristics to develop new treatments. MATERIAL AND METHODS: A new human GBM cell line, named R2J, was established from the cerebro-spinal fluid of a patient affected by GBM with leptomeningeal metastasis. Cells were cultured both in monolayer and in spheres in a medium without serum and characterized before being implanted into the striatum of nude mice. The tumor progression was followed by MRI and brains were collected to perform IHC analyses. Sodium selenite (SS), previously described for its anticancer potential in GBM cell lines, was tested in the R2J cells prior to delimitate its toxicity and absorption in Balb/c mice. To be achieved, we tested different doses of SS (2.25, 4.5, 6.75 and 10.125 mg/kg-dissolve in water-) given orally for 5 days followed by a wash-out of 2 days followed by 5 supplementary days. At the end of this protocol, mice were sacrificed to collect blood, brain, kidney, liver and lungs. We evaluated the behavior and the weight of the mice along the study and we performed biochemical measurements including the dosage of selenium (Se) in blood and organs by ICP-MS. RESULTS: R2J cells displays an abnormal karyotype and about 2% of the population is able to form self-renewable spheres in a define medium. Original tumor, R2J cells cultured in monolayer (2D) and in spheres showed a persistence expression of CD44, CD56 (except in monolayer), EGFR, Ki67, Nestin, and vimentin. The R2J cell line is tumorigenic and possesses CSC properties. We tested in vitro the anticancer effects of sodium selenite (SS) compared to temozolomide (TMZ). SS was absorbed by R2J cells, was cytotoxic, induced an oxidative stress, and arrested cell growth in G2M before inducing both necrosis and apoptosis via caspase-3. SS also changed dimethyl-histone-3-lysine-9 (H3K9m2) levels and reduced histone deacetylase (HDAC) activity, suggesting anti-invasiveness potential. Mouse orthotopic xenografts of R2J cells were able to form tumor within 14 days, even when implanted at 1000 cells as spheres. IHC revealed a persistent CD56 and nestin expression as in the parental tumor. After the period of treatment with SS, mice lost about 5% of their weight at 6.75 mg/kg. Se concentration significantly increased in plasma in a dose dependent manner, in kidney (at 2.25 mg/kg), in liver (at 4.5mg/kg), in brain and lung (at 6.75 mg/kg). CONCLUSION: This study highlights the value of this new GBM cell line for preclinical modeling and allowed us to test SS as a potential anticancer agent. All these data plus the fact that Se crosses the blood brain barrier are the first step to further investigations in orthotopic patient-derived glioblastoma xenografts in mice.